Morphology of the forelimb of Psilopterus bachmanni (Aves, Cariamiformes) (Early Miocene of Patagonia) - Degrange, Federico Javier (2015)
Psilopterines are the smallest and most gracile predatory birds belonging to the large terrestrial Phorusrhacidae, which were abundant during the South American Tertiary. Two taxa are recognized from the Santacrucian (late Early Miocene) beds of Argentinian Patagonia: Psilopterus lemoinei and Psilopterus bachmanni. Although the first species was recently redescribed and is well known, in the case of P. bachmanni, the smaller of the two, the forelimb skeleton was virtually unknown until recently. The fossils described herein come from the coast of Santa Cruz Province, and were recovered from the middle levels of the Estancia La Costa Member, Santa Cruz Formation. The specimen includes associated bones of both forelimbs and a fragmentary furcula. The manus of this species, previously unknown, is described here for the first time: the os carpi ulnare and radiale are very stout bones, the carpometacarpus has processi extensorius and alularis very marked and stout and the os metacarpale majus and phalanges digiti majoris are very robust, and the phalanx digiti minoris is flattened. It has been proposed that some species belonging to Psilopterus were able to fly in a clumsy manner. While this work is not intended to certify this condition through complex models, some considerations of the paleobiology of P. bachmanni based on manus movement capabilities and body mass are presented. It seems plausible that P. bachmanni would have had both cursorial and flying capabilities. The information provided here represents an effort to discuss features previously unknown in phorusrhacids and to provide new data that may be useful in future systematic, morpho- functional and evolutionary studies